Applying quantum mechanics for extreme value prediction of VaR and ES in the ASEAN stock exchange - Chukiat Chaiboonsri; Satawat Wannapan (Economies, 2021)
The advantage of quantum mechanics to shift up the ability to econometrically understand extreme tail losses in financial data has become more desirable, especially in cases of Value at Risk (VaR) and Expected Shortfall (ES) predictions. Behind the non-novel quantum mechanism, it does interestingly connect with the distributional signals of humans' brainstorms. The highlighted purpose of this article is to devise a quantum-wave distribution methodically to analyze better risks and returns for stock markets in The Association of Southeast Asian Nations (ASEAN) countries, including Thailand (SET), Singapore (STI), Malaysia (FTSE), Philippines (PSEI), and Indonesia (PCI). Data samples were observed as quarterly trends between 1994 and 2019. Bayesian statistics and simulations were applied to present estimations' outputs. Empirically, quantum distributions are remarkable for providing "real distributions", which computationally conform to Bayesian inferences and crucially contribute to the higher level of extreme data analyses in financial economics.
Keywords: 330; quantum mechanics; wave function; extreme value analysis; Bayesian inference; stock market; Value at Risk (VaR); Expected Shortfall (ES); prediction